Exploration and Identification of the Entomopathogenic Fungus Metarhizium anisopliae in Corn Plants in Sebandung Village, Sukorejo, Pasuruan - Rateh Lailatul Risdiyanti; Wiludjeng Widayati; Penta Suryaminarsih (Nusantara Science and Technology Proceedings, 2021)
Metarhizium anisopliae is a biological control agent (BCA) that have been developed to control plant pest in this disruption era. These fungi penetrate the insect body through its skin between the head and the thoraxs also in between the joint. The purpose of this research is to identify the characteristic of the fungi M. Anisopliae from the exploration in sebandung village, sub-district Sukorejo, district Pasuruan. Data analysis is done by using descriptive data. Step of the research involves (1) sample gathering from the soil in the cornfield that has been predicted to have BCA biodiversity, after that determined 5 sampling points diagonally, each sample contains 100 gr of soil from the depth of 10 -20 cm, (2) fungi baiting by using a mealworm (Tenebrio Molitor) as a bait, (3) M. Anisopliae isolate using PDA (Potato Dextrose Agar), (4) identification is conducted by macroscopic and microscopic. The identification result shows that the isolate has a white mycelium that forms into a mossy green spore, fine texture, easily spread, and insulated mycelium, straight conidiophore, hyalin, and branching, single-cell conidia, hyalin, round cylinder type, also white to the mossy green colony. Parasitism test results show that T.molitor larvae develop a hard body, have a murky color, covered in white hyphea till it transforms into moosy green spore with a fine texture and easily spread, the spore is the final form of the fungi propagule existence in the host as a survival phase in extreme condition.